1956: Deleuze and Foucault in the Archives, or, What Happened to the A Priori?. Issue 2 (May 2021) - Gray, Chantelle
Abstract : When Gilles Deleuze, in his book on Michel Foucault, asks, 'who would think of looking for life among the archives?', he uncovers something particular to Foucault's philosophy, but also to his own: a commitment to the question of what it means to think, and think politically. Although Foucault and Deleuze, who first met in 1952, immediately felt fondness for each other, a growing animosity had settled into the friendship by the end of the 1970s – a rift deepened by theoretical differences. Notwithstanding these difficulties, Foucault and Deleuze shared a love for Nietzsche, as well as a curious fascination with Kant. Kant's influence, which was met with more opposition, is precisely the tension I tease out in this article, showing how Foucault critiques Kant's a priori through his own concept of the historical a priori, along with regularity and resistance, while Deleuze and Guattari, if more obliquely, critique Kant's a priori by further developing Foucault's notion of the historical a priori through their own method of pragmatics, particularly in three chapters of A Thousand Plateaus, namely 'The Geology of Morals', 'Postulates of Linguistics' and 'On Several Regimes of Signs'. What I am interested in, then, is Deleuze and Guattari's treatment of redundancy, a concept mentioned seventy times in A Thousand Plateaus. Although not one of their main or most developed concepts, redundancy is a thread that can be traced back to Deleuze's first book, Empiricism and Subjectivity . Moreover, their more developed concepts, for example the diagram, the abstract machine, becoming, micro-politics and the ritornello, as well as their political philosophy, are grounded in their understanding of redundancy, which moves their philosophy beyond mapping out the conditions of possibility (Kant) and demonstrating that the historical a priori emerges as a contingent function of its own expression (Foucault) to the genesis of thought.